2015
DOI: 10.1136/vr.102916
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antileptospiral serum antibodies in dogs in Ireland

Abstract: A total of 474 serum samples from client owned Irish dogs were tested for the presence of antibodies to serovars Canicola, Icterohaemorrhagiae, Bratislava, Autumnalis, Pomona, Altodouro, Grippotyphosa, Mozdok, Hardjobovis and Ballum. Six per cent of dogs presented to veterinary practitioners for problems unrelated to leptospirosis showed evidence of prior exposure to leptospiral serovars belonging to the serogropus Ballum, Australis, Pomona and Sejroe. One unvaccinated dog suspected to have leptospirosis showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
9
1
Order By: Relevance
“…In dogs the disease shows at least three different pathologic syndromes: icteric syndrome, uremic syndrome and hemorrhagic syndrome (Adler and de la Peña-Moctezuma, 2010). Seroprevalence in cattle may be as high as 84% and in dogs 35% (de Freitas et al, 2010, Ellis et al, 1986b, Oliveira Lavinsky et al, 2012, Schuller et al, 2015. Lower incidences have been found in other domestic animals among them sheep acting mainly as asymptomatic reservoirs (Cerri et al, 1996, Ellis et al, 1994, Lilenbaum et al, 2009; in horses the disease usually has a chronic course resulting in recurrent uveitis (ERU) being the main cause of equine blindness (Halliwell et al, 1985, Malalana et al, 2015, Wollanke et al, 2001.…”
Section: Human Animal and Environmental Reservoirsmentioning
confidence: 99%
“…In dogs the disease shows at least three different pathologic syndromes: icteric syndrome, uremic syndrome and hemorrhagic syndrome (Adler and de la Peña-Moctezuma, 2010). Seroprevalence in cattle may be as high as 84% and in dogs 35% (de Freitas et al, 2010, Ellis et al, 1986b, Oliveira Lavinsky et al, 2012, Schuller et al, 2015. Lower incidences have been found in other domestic animals among them sheep acting mainly as asymptomatic reservoirs (Cerri et al, 1996, Ellis et al, 1994, Lilenbaum et al, 2009; in horses the disease usually has a chronic course resulting in recurrent uveitis (ERU) being the main cause of equine blindness (Halliwell et al, 1985, Malalana et al, 2015, Wollanke et al, 2001.…”
Section: Human Animal and Environmental Reservoirsmentioning
confidence: 99%
“…Leptospirosis in dogs has been associated with serovars Canicola and Icterohaemorraghiae but it is now clear that dogs are susceptible to infection with multiple serovars (Schuller et al., 2015a). In Europe, Grippotyphosa and Bratislava have emerged as major causes of canine leptospirosis (Ellis, 2010; Mayer-Scholl et al., 2013; Renaud et al.…”
Section: Introductionmentioning
confidence: 99%
“…from dogs to humans. Dogs could serve as an important sentinel specie for human infection, as well as indicator of the presence of leptospires in specific environments (Ghneim et al., 2007; Major et al., 2014; Schuller et al., 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…Although the inclusion of serogroup Icterohaemorrhagiae in vaccine formulations has led to its decreasing seroprevalence in Italy [ 46 ], this serogroup is still a major cause of disease in dogs, owing to the ubiquitous nature of its maintenance host. The dog, in this case, represents a spill-over and can be used as an important sentinel species for human and other animal infections [ 51 , 52 , 53 ]. Interestingly, the IZSLER database revealed that Leptospira ST17 occurs in different hosts (mouse, cat, hedgehog, horse, goat and cow), which indicates its ability to cause infection in a wide range of animal species.…”
Section: Discussionmentioning
confidence: 99%